Efficacy of a repeat testing protocol for cognitive fatigue assessment: a preliminary study in postconcussive syndrome participants - Thomas F Rau; Sarjubhai A Patel; Erik E Guzik; Edmond Sorich; Alan J Pearce (Concussion, 2017)
Aim: A small but notable number of individuals who suffer a concussion report ongoing cognitive difficulties. This preliminary study investigated the efficacy of repetitive test application to disc...